Customer Satisfaction Analysis of Sekolah Alam In Depok and Its Implication To Word of Mouth - Rizki Arianto; Prasetyo Hadi; Alfatih S Manggabarani (Syntax Literate, 2022)
The increasing number of schools in Depok in the latest 5 years, forcing the Sekolah Alam Depok to fight in a tight competition. Decreasing the number of registrants in Sekolah Alam Depok is suspiciously caused by the decreasing of Customer satisfaction and the lack the Customer intention in promoting and recommending Sekolah Alam to others. The purpose of this study was to analyse empirically the effect of the Service Quality on the tendency of customer to do Word of Mouth either directly or indirectly through Customer Satisfaction. The research is an empirical study with quantitative approach. The instrument is a questionnaire and analysed by using SEM with smartPLS software. The main result of this study revealed that word of mouth will be more directly influenced by quality service than indirectly through customer satisfaction. Based on the coefficient of influence, where the quality of service has a coefficient of influence of 49.1% directly on word of mouth while the service quality if through customer satisfaction has a coefficient of influence of 17.7% on word of mouth. it shows that actually good quality of service is the key to create word of mouth, and customer satisfaction proved not to have a large impact to increase word of mouth. The conclusion of this study is that good service quality will have implications for the creation of word of mouth either directly or indirectly through customer satisfaction.